Impacto econômico dos fatores políticos nos municípios cearenses - Castro, Rubens de Oliveira (2017)
The purpose of this study was measure the impact of of the reelection amendment in the economic development of the municipalities of Ceará. After the reelection was amended, it was possible for the candidates to defend their mandates and again to compete for the same position in the executive. In the economic literature there is no consensus on the impacts of reelection on economic growth. Thus, this work had as its main objective to measure the impacts of this reelection in the increase of GDP per capita in the municipalities of Ceará. For that, the panel data method was used, based on an economic growth model that uses physical and human capital as determinants of economic growth. The results concluded that human and physical capital have an influence on GDP growth per capita. But it was not possible to establish any relation of this growth with the permanence or not of a political group in the control of public positive input on management, but the alignment of mayors with the governor or the president showed per capita GDP.